S20-4: Equitable Recruitment of Expert and Citizens Councils: Guidance From the IMPAQT Project on Physical Activity Policy Benchmarking (Baltic Journal of Sport and Health Sciences, 2026)
Purpose: The health promotion community is increasingly recognising the need for better policies to reduce inequities in physical activity. The IMPAQT project aims to address this issue by integrating equity aspects into an existing policy monitoring tool, the PA-EPI. This is done with the support of stakeholder councils composed of policymakers, experts, and citizens. To assure that the development process itself remains equitable, the adequate representation of all relevant perspectives in these councils is key. IMPAQT therefore conducted an exploratory study to develop guidelines for the equitable recruitment of stakeholder councils for future users of the PA-EPI.Methods: We employed a mixed-methods approach consisting of a grey literature search for existing guidelines and three expert interviews. For the literature review, we ran a keyword-based search on Startpage, exploring first 100 listed websites and systematically documenting the relevant information of the included results. We then conducted semi-structured interviews with three renowned health equity experts. Interviews were transcribed and analysed based on categories previously identified by the IMPAQT team.Results: Seventy-one out of the 100 screened websites were identified as potentially relevant. Sources mostly contained general considerations on addressing power imbalances in health promotion but no detailed guidelines on equitable recruitment. By contrast, the interviewed experts provided recommendations on: (a) how to define equity in the context of the councils, (b) the limits of equitable representation, and (c) specific strategies for equitable council recruitment. They identified citizen involvement as a particular challenge and recommended to either use the national-level NGOs to represent different interests or local-level citizen councils with tailored task descriptions to bridge the gap between people’s everyday lives and the abstract demands of national-level policy benchmarking.Conclusion: While this study cannot provide comprehensive guidelines on equitable recruitment in participatory physical activity promotion processes, results provide some valuable guidance on how to frame equity for such processes, manage expectations for equitable recruitment, and how to approach organisations and citizens to enlist their support. In particular, future policy benchmarking endeavours may benefit from the proposed strategies for citizen involvement.